فعالية التغطية لمدة ساعتين يومياً في علاج الغمش المعتدل عند الأطفال - درويش تيم (Latakia University Journal -Medical Sciences Series, 2013)
الهدف من البحث هو دراسة فعالية التغطية لمدة ساعتين يوميا عند الأطفال بين عمر 4 و 9 سنوات في علاج الغمش المعتدل. شارك بالدراسة 20 طفلاً تتراوح أعمارهم بين 4 و 9 سنوات ولديهم غمش معتدل، إذ تتراوح القدرة البصرية بين 0.2 و 0.5 . تم تغطية العين السليمة لمدة ساعتين يوميا مع إجراء تمارين للعمل القريب لمدة ساعة في أثناء التغطية. حدث تحسن بالقدرة البصرية بالعين الكسولة بمقدار (2.5 ) سطرين ونصف عند الشهر الرابع. في الشهر الرابع كانت القدرة البصرية 0.65 على الأقل و حدث تحسن بمقدار 3 أسطر أو أكثر عند 65% من الأطفال. عند 80% من الأطفال كان هناك تحسن بمقدار سطرين أو أكثر. يمكن الاستنتاج أن تغطية العين الكسولة لمدة ساعتين يوميا مع إجراء تمارين للعمل القريب لمدة ساعة يعتبر فعالا في علاج الغمش المتوسط عند الأطفال بعمر 4 إلى 9 سنوات. The aim is to study the efficacy of 2 hours of daily patching for treating moderate amblyopia in children aged 4 to 9 years. 20 children aged 4 to 9 years who have moderate amblyopia (visual acuity between 0.2 to 0.5) participated in the study. They receive 2 hours of daily patching combined with 1 hour of near visual acuity activities during patching. The visual acuity in the amblyopic eye improved from baseline to 4 month by 2.5 lines. The 4 month visual acuity was at least 0.65 and improved from the baseline by 3 or more lines in 65% of children. The visual acuity improved by 2 or more lines in 80% of children. It could be concluded that 2 hours of daily patching combined with 1 hour of near visual acuity activities during patching is effective in treating moderate amblyopia in children aged 4 to 9 years